Selection of extra-early maize inbreds under low N and drought at flowering and grain-filling for hybrid production - Badu-Apraku, Baffour; Fakorede, M.A.B.; Oyekunle M; Akinwale, R. (2011)
Extra-early maize (Zea mays L) tolerant to low-N and drought could stabilize yields in sub-Saharan Africa. Studies were conducted under drought and low-N conditions in Nigeria for three years to determine the potential of 90 extra-early inbreds for hybrid production and evaluate the performance of 36 hybrids derived from the inbreds under drought at flowering and grain-filling periods and well-watered conditions. Results showed significant ge¬notypic mean squares for grain yield and most other traits of the inbreds under drought and/or low-N conditions. TZEEI6, TZEEI4, TZEEI36, and TZEEI38 were identified as ideal inbreds under drought. Under low-N, TZEEI19, TZEEI96 and TZEEI45 were top ranking with TZEEI19 as the ideal inbred. TZEEI19, TZEEI29, TZEEI56, TZEEI38, and TZEEI79 were tolerant to both stresses. Eighteen of the 36 hybrids produced above-average yields across environments with four hybrids identified as very stable. TZEEI29 x TZEEI21 was the closest to the ideal geno¬type because it combines large mean performance with high yield stability. Hybrid yield under drought had large positive correlation with grain yield under well-watered environments. Selection for inbred traits such as days to silking and anthesis-silking interval under drought predicted fairly accurately hybrid yield under well-watered environments. It was concluded that extra-early inbreds and hybrids are not only drought escaping but also possess drought and low-N tolerant genes.